Combination of triple chemotherapy and sequential re-irradiation as salvage for recurrent treatment-refractory hemangiopericytoma of extraspinal dura: a case report - Wang, Min; Lv, Wanrui; Chen, Xi; Cheng, Ke (Frontiers in Oncology, 2024)
IntroductionHemangiopericytoma (HPC) in the central nervous system (CNS) is rare. Our report aims to present an HPC case with multiple surgeries at the lumbar spine, and demonstrates an effective treatment as salvage.Case reportIn this report, we present the case of a young girl with recurrent meningeal invasion of lumbar spinal HPC. The patient underwent multiple surgeries to remove the tumors, and adjuvant radiotherapy was administered after the initial resection. And it presented a pathological anaplastic transformation with subsequent accelerated recurrence. A combination therapy approach involving triple chemotherapy and sequential re-irradiation was found to be effective as salvage treatment at the third recurrence.ConclusionsSurgical resection remains the primary treatment modality for HPC in the spine, despite its high tendency for local recurrence and the risk of metastasis. For unresectable recurrent HPC, combining chemotherapy and sequential re-irradiation might be a highly effective, and safe reference regimen as the salvage treatment for the refractory case.